Hospitality and Re-Orientalist Thresholds: Amit Chaudhuri Writes Back to India - Lau, Lisa (2018)
In times of heightened, no-longer-linear migratory flows, when migrations oscillate and even double back on their own routes, this article interrogates the unwritten social contract of hospitality between host and guest. Taking as a case study Amit Chaudhuri’s returnee narrative, Calcutta: Two Years in the City (2013)—his personal account of relocation to India—this paper juxtaposes the mismatch between hospitalities assumed and experienced, from India’s lukewarm hospitality to the expectations of its elite (even celebrity) sojourner authors, now diasporic returnee migrants. The article highlights the tensions in negotiating host–guest roles, particularly when insider–outsider, stranger–native boundaries blur. It also raises the question of whether some degree of re-orientalism is therefore inevitable in the cosmopolitan returnee’s perceptions and subsequent representations of what was once ‘home’ and now is ‘home again’.